2016
DOI: 10.1378/chest.15-0529
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of All-Cause Mortality in Patients With Severe COPD and Major Depression Admitted to a Rehabilitation Hospital

Abstract: BACKGROUND: COPD is a major cause of all-cause mortality. We examined predictors of 1-year mortality in patients with severe COPD and major depression after inpatient treatment in a rehabilitation hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 41 publications
1
23
0
1
Order By: Relevance
“…68 Anxiety and depression contribute to the substantial burden of COPD-related morbidity and are associated with more impaired quality of life and reduced adherence to treatment. 69,70 Women with COPD report higher levels of anxiety and depression than men with COPD, furthering the burden of COPD in women. 56,66,[71][72][73] COPD exacerbations are associated with morbidity, mortality, resource burden, and health-care costs.…”
Section: Focusing On the Patient: How Does Copd Affect Women?mentioning
confidence: 99%
“…68 Anxiety and depression contribute to the substantial burden of COPD-related morbidity and are associated with more impaired quality of life and reduced adherence to treatment. 69,70 Women with COPD report higher levels of anxiety and depression than men with COPD, furthering the burden of COPD in women. 56,66,[71][72][73] COPD exacerbations are associated with morbidity, mortality, resource burden, and health-care costs.…”
Section: Focusing On the Patient: How Does Copd Affect Women?mentioning
confidence: 99%
“…A study including stable patients with COPD even showed that drawing impairment predicted increased mortality risk [66]. Nevertheless, Yohannes et al found that MMSE scores did not predict 1-year all-cause mortality [67]. Moreover, only a modest association was found between executive function and survival in the NETT trial [65].…”
Section: Health Outcomesmentioning
confidence: 99%
“…Severe lung function impairment [10] High partial pressure of carbon dioxide [10] Severe dyspnoea [19] Impaired quality of life [11] Physical disability [11,19] Depression [11,13,16,22] Long-term oxygen therapy [11,14] Anxiety [16] Chronic heart failure [14,21] Falls and history of falls [19] Reduced exercise capacity [11]…”
Section: Clinically Relevant Markersmentioning
confidence: 99%